Implementación de la pirosecuenciación en las poblaciones virales de pacientes con VIH-1 en Ecuador - Gonzalez-Gonzalez, Manuel Augusto; Hermida-Álava, Katherine Stephania; Correa-Sierra, Consuelo Beatriz; Gómez-Andrade, Luis Fernando; Machado Diaz, Ana Cecilia; Castillo-Segovia, Martha; Pérez-Santos, Lissette; Kourí-Cardella, Vivian (Revista Cubana de Medicina Tropical, 2017)
Objective: implement the pyrosequencing system Roche/454 for the gene pol of HIV-1. Methods: based on plasma samples from 33 Ecuadorian HIV-1 positive patients with antiretroviral therapy failure, pyrosequencing was conducted and the results were analyzed with the DeepCheck software. Results: results were obtained for 27 of the 33 samples analyzed. Twenty-five mutations were found to be associated to resistance in viral populations. The most common were F77L, M184V/I, K103N/S, M46L/I, I50V/L, Q58E, V82T/F/A/S/L and L90M. High resistance was observed to non-nucleoside reverse transcriptase inhibitors and to protease inhibitors (43.5 and 44.4 %, respectively, in minority populations), as well as to protease inhibitors in majority populations (26.4 %). 2, 2 and 1 samples were detected with full resistance to each drug type (nucleoside reverse transcriptase inhibitors, non-nucleoside reverse transcriptase inhibitors and protease inhibitors, respectively) in majority populations, and 3, 4 and 6 in minority populations, as well as 2 viruses with resistance to the three drug groups in minority populations. Most samples belonged to subtype B (77.8 %) in each of the study regions. Conclusions: the study allowed implementation of the pyrosequencing system, which made it possible to analyze the first data on resistance to antiretrovirals in Ecuador.